Effectiveness of integrating cervical cancer prevention strategies into HIV care programmes: A mixed-methods systematic review protocol. - Kimeshnee Govindsamy; Susanne Noll; Ntombifuthi Blose; Edina Amponsah-Dacosta (PLoS ONE)
Introduction Cervical cancer, which is the fourth most frequently diagnosed cancer among women globally, remains a significant health burden despite being preventable and treatable, exposing gaps in accessing prevention and control services. Adolescent girls and young women (AGYW) living with HIV face heightened risk of persistent HPV infection, a primary cause of cervical cancer, making this population the ideal target for preventing cervical cancer before HPV exposure or disease progression. The overlap of cervical cancer and HIV exacerbates public health challenges, urging intensified efforts in bolstering prevention and control measures. Integration of cervical cancer prevention strategies into HIV care programs shows promise in effectively addressing this dual burden. Methods To evaluate the effectiveness of integrating cervical cancer prevention strategies within HIV care programs, a mixed-methods systematic review will be conducted. A comprehensive Boolean search for literature published and indexed in PubMed, Cochrane Library, EBSCO Host, Web of Science, Scopus, and Google Scholar will be conducted, without imposing any language restrictions. This review will be conducted in alignment with the Joanna Briggs guidelines on systematic reviews together with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Data from eligible studies will be extracted and synthesized, and their quality assessed. Discussion There is limited understanding of the effectiveness of integrating cervical cancer prevention and HIV care in the real-world setting. While some studies touch on integration, focus tends to be on cervical cancer screening alone, neglecting vaccination, treatment of precancerous lesions, and education programs. Previous reviews on this focus are outdated, surpassing six years. This systematic review aims to fill these evidence gaps by thoroughly evaluating the challenges and opportunities associated with integrating the full complement of HPV prevention strategies and HIV care programs. The anticipated findings could enhance service delivery models aimed at reducing cervical cancer incidence and mortality among AGYW living with HIV. Trial registration Systematic review registration: PROSPERO registration number: CRD42024535821.